The two-year course of late-life depression; results from the Netherlands study of depression in older persons - Comijs, Hannie C (BMC Psychiatry, 2015)
BACKGROUND: We aimed to examine the course of depression during 2-year follow-up in a group clinically depressed older persons. Subsequently, we studied which socio-demographic and clinical characteristics predict a depression diagnoses at 2-year follow-up. METHODS: Data were used from the Netherlands Study of Depression in Older persons (NESDO; N = 510). Diagnoses of depression DSM-IV-TR criteria were available from 285 patients at baseline and at 2-year follow-up. Severity of the depressive symptoms, as assessed with the Inventory of Depressive Symptoms (IDS), was obtained from 6-monthly postal questionnaires. Information about socio-demographic and clinical variables was obtained from the baseline measurement. RESULT: From the 285 older persons who were clinically depressed at baseline almost half (48.4%) also suffered from a depressive disorder two years later. Patients with more severe depressive symptoms, comorbid dysthymia, younger age of onset and more chronic diseases were more likely to be depressed at 2-year follow-up. 61% of the persons that were depressed at baseline had a chronic course of depressive symptoms during these two years. CONCLUSIONS: Late-life depression often has a chronic course, even when treated conform current guidelines for older persons. Our results suggest that physical comorbidity may be candidate for adjusted and intensified treatment strategies of older depressed patients with chronic and complex pathology.